Neuropsychiatric symptoms as risk factors of dementia in a Mexican population: A 10/66 Dementia Research Group study. Issue 3 (10th October 2017) - Acosta, Isaac; Borges, Guilherme; Aguirre‐Hernandez, Rebeca; Sosa, Ana Luisa; Prince, Martin
Abstract: Introduction: Cognitive and/or memory impairment are the main clinical markers currently used to identify subjects at risk of developing dementia. This study aimed to explore the relationship between the presence of neuropsychiatric symptoms and dementia incidence. Methods: We analyzed the association between neuropsychiatric symptoms and incident dementia in a cohort of 1355 Mexican older adults from the general population over 3 years of follow‐up, modeling cumulative incidence ratios using Poisson models. Results: Five neuropsychiatric symptoms were associated with incident dementia: delusions, hallucinations, anxiety, aberrant motor behavior, and depression. The simultaneous presence of two symptoms had a relative risk, adjusted for mild cognitive impairment, diabetes, indicators of cognitive function, and sociodemographic factors, of 1.9 (95% confidence interval, 1.2–2.9), whereas the presence of three to five, similarly adjusted, had a relative risk of 3.0 (95% confidence interval, 1.9–4.8). Discussion: Neuropsychiatric symptoms are common in predementia states and may independently contribute as risk factors for developing dementia. Highlights: Not only cognitive impairment and cognitive features are useful in identifying older adults at risk for developing dementia. Of the 12 neuropsychiatric symptoms evaenated, 5 were associated with incident dementia (delusions, hallucinations, depression, anxiety, and aberrant motor behavior) in a 3‐year follow‐up. The evaluation of neuropsychiatric symptoms, along with other simple, practical, and inexpensive features, may be useful in identifying subjects at risk of dementia in community health settings and by general practitioners.